Hak Atas Tanah yang Diambilalih Kembali oleh Ahli Waris dalam Transaksi Jual Beli Melalui PPAT (Studi Kasus Putusan Mahkamah Agung Nomor 890 K/Pdt/2019) - Aviliani Nur Aulia; FX. Arsin Lukman (LPPM Universitas Ekasakti Padang, 2023)
The sale and purchase transaction of land rights carried out by the heirs as sellers and buyers through the Land Deed Official (PPAT) was not known by the heirs. Thus, giving rise to a lawsuit against the heirs because the land sale and purchase transaction should be able to transfer back into the hands of the heirs, but the judge's consideration rejected it because the lawsuit was blurred and the object of the dispute was unclear. As well as not in accordance with Article 1870 of the Civil Code that this is based on the lack of evidence provided by the heirs as Article 180 HIR adheres to the principle of hereditatis petition where the strength of the heirs still plays an important role as there is a legietieme portie Article 913 of the Civil Code, the second lawsuit lacks parties in the AJB transaction process by PPAT as Article 22 of PP No. 37 of 1998 concerning Regulations on the Position of Land Deed Officials This research was conducted based on quantitative methods that are descriptive quantitative methods. Thus, Decision Number 69/Pdt.G/2017/PN.NJK at the first level in this case does not explain in detail the legal grounds that resulted in the lawsuit being rejected, so that legal protection is needed for landowners of land objects who carry out the sale and purchase transaction process through PPAT with the presence of parties who participate as witnesses in the signing of land objects.